The multipole form Factors and the Influence of the Weak Interaction in \(e^-- ^6 L i\) Elastic Scattering at High Energies : A Recent Study - M. T. Vo (Fundamental Research and Application of Physical Science Vol. 3, 2023)
At the energies of GeV the electron-nucleus scattering cross section, which is calculated through multipole form factors, includes the electromagnetic interaction part and the weak interaction part. To date, the pseudo-vector weak form factors have only been approximated by impulse approximation. In this study, precise calculations for all multipole form factors are performed in the scattering of unpolarized electrons by unoriented nuclei using the multiparticle shell model. By using the formulas to calculate the reduced matrix elements of tensor operators, the formulas for calculating multipole form factors of nuclei with six nucleons are completely set up. Applying the given formulas, the author has also determined all multipole form factors that are present in \(e^-- _3^6 L i\) elastic scattering cross section when the nucleus is in ground state. Based on the calculated multipole form factors, the influence of weak interaction is investigated corresponding to different incident electron energies in the framework of Glashow-Weinberg-Salam (GWS) model.